A novel peptide interferes with Mycobacterium tuberculosis virulence and survival. Issue 1 (7th August 2014) - Samuchiwal, Sachin Kumar; Tousif, Sultan; Singh, Dhiraj Kumar; Kumar, Arun; Ghosh, Anamika; Bhalla, Kuhulika; Prakash, Prem; Kumar, Sushil; Trivedi, Ashish Chandra; Bhattacharyya, Maitree; Das, Gobardhan; Ranganathan, Anand
Abstract : Tuberculosis (TB) is a huge global burden, with new and resistant strains emerging at an alarming rate, necessitating an urgent need for a new class of drug candidates. Here, we report that SL3, a novel 33‐amino acid peptide, causes debilitating effects on mycobacterial morphology. Treatment with SL3 drastically inhibits the growth of Mycobacterium tuberculosis in vitro as well as in a pre‐clinical mouse model for M.tb infection. Microarray analysis of SL3‐expressing strain demonstrates wide‐scale transcriptional disruption in M.tb . We therefore believe that SL3 and similar peptides may herald a new approach towards discovering new molecules for TB therapy. Abstract : The novel peptide SL3 is a strong binder of the virulence‐determining protein ESAT‐6. SL3 caused debilitating effects on mycobacterial growth and morphology. SL3 led to accelerated clearance of M.tb and lowered immune response in a pre‐clinical mouse model. Microarray analysis of the mutant strain demonstrated a wide‐scale transcriptional disruption caused by SL3 in M.tb .